Incidence of innovation in the export of silver jewelry in Peru - Carruitero Honores, Maribel (2021)
The objective of this article was to evaluate the extent to which innovation affects Peruvian silver jewelry exports from 2015 to 2019. For this, a non-experimental correlational study was carried out through interviews with companies that, as a whole, represented 67% of silver jewelry exports from Peru to the world. The results allowed to conclude that the innovation had a positive impact on the exports of silver jewelry from Peru, by applying technological information methods in relation to the use and processing of data in 2016; Likewise, when considering the development of products and business processes in the future in the years 2015 and 2019, provided that said activities are based on research. Consequently, the increase in exports of the silver jewelry sector is associated with the management capacity of companies to introduce strategies that allow the development of innovation in specific processes to achieve their goals in a global market.